Serum urea increase during hospital stay is associated with worse outcomes after in-hospital cardiac arrest - Barros, João Carlos Clarck [UNESP]; Ferreira, Gustavo Martins [UNESP]; Souza, Isabelle de Almeida [UNESP]; Shalova, Asiya [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Zornoff, Leonardo [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Favero, Edson Luiz [UNESP]; Lazzarin, Taline [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Elsevier, 2024)
Background: Evaluate the association between serum urea at admission and during hospital stay with return of spontaneous circulation (ROSC) and in-hospital mortality in patients with in-hospital cardiac arrest (IHCA). Methods: This retrospective study included patients over 18 years with IHCA attended from May 2018 to December 2022. The exclusion criteria were the absence of exams to calculate delta urea and the express order of “do-not-resuscitate”. Data were collected from the electronic medical records. Serum admission urea and urea 24 hours before IHCA were also collected and used to calculate delta urea. Results: A total of 504 patients were evaluated; 125 patients were excluded due to the absence of variables to calculate delta urea and 5 due to “do-not-resuscitate” order. Thus, we included 374 patients in the analysis. The mean age was 65.0 ± 14.5 years, 48.9% were male, 45.5% had ROSC, and in-hospital mortality was 91.7%. In logistic regression models, ROSC was associated with lower urea levels 24 hours before IHCA (OR: 0.996; CI95%: 0.992-1.000; p: 0.032). In addition, increased levels of urea 24 hours before IHCA (OR: 1.020; CI95%: 1.008-1.033; p: 0.002) and of delta urea (OR: 1.001; CI95%: 1.001-1.019; p: 0.023) were associated with in-hospital mortality. ROC curve analysis showed that the area under the ROC curve for mortality prediction was higher for urea 24 hours before IHCA (Cutoff > 120.1 mg/dL) than for delta urea (Cutoff > 34.83 mg/dL). Conclusions: In conclusion, increased serum urea levels during hospital stay were associated with worse prognosis in IHCA.
Keywords: Cardiac arrest; Mortality; Return of spontaneous circulation; Urea